The Economy of Promises : Trust, Power, and Credit in America - Carruthers, Bruce G. (Princeton University Press, 2022)
A comprehensive and illuminating account of the history of credit in America--and how it continues to divide the haves from the have-notsThe Economy of Promises is a far-reaching study of credit in nineteenth- and twentieth-century America. Synthesizing and surveying economic and social history, Bruce Carruthers examines how issues of trust stitch together the modern U.S. economy. In the case of credit, that trust involves a commitment by debtors to repay money they have borrowed from lenders. Each promise poses a fundamental question: why does the lender trust the borrower?The book tracks the dramatic shift from personal qualitative judgments to the impersonal quantitative measurements of credit scores and ratings, which make lending on a much greater scale possible. It discusses how lending is shaped by the shadow of failure, and the possibility that borrowers will break their promises and fail to repay their debts. It reveals how credit markets have been shaped by public policy, regulatory changes, and various political factors. And, crucially, it explains how credit interacts with economic inequality, contributing to vast and enduring racial and gender differences--which are only exacerbated by the widespread use of credit scores and ratings for "big data" and algorithmic decision-making. Bringing to life the complicated and abstract terrain of human interaction we call the economy, The Economy of Promises is an important study of the tangle of indebtedness that, for better or worse, shapes and defines American lives